Simple and rapid monitoring of doxorubicin using streptavidin-modified microparticle-based time-resolved fluorescence immunoassay. Issue 28 (25th April 2018) - Liang, Junyu; Zhang, Zhigao; Zhao, Hui; Wan, Shanhe; Zhai, Xiangming; Zhou, Jianwei; Liang, Rongliang; Deng, Qiaoting; Wu, Yingsong; Lin, Guanfeng
Abstract : Simple, rapid SA-MPs based TRFIA, is applied in therapeutic drug monitoring and the analytical performance is comparable with LC-MS/MS. Abstract : Developing a simple analytical method suitable for therapeutic drug monitoring in a clinical setting is key to establishing guidelines on accurate dose administration and the advancement of precision medicine. We devised a simple rapid analytical method through the combination of streptavidin-modified microparticles and a time-resolved fluorescence immunoassay for therapeutic drug monitoring. The analytical performance of this method was investigated and validated using clinical samples. By determination of doxorubicin concentration, the proposed assay has shown a satisfactory linear range of detection (3.8–3000 ng mL −1 ) with a limit of detection of 3.8 ng mL −1 and an IC50 of 903.9 ng mL −1 . The intra and inter-assay coefficients of variation were 4.12–5.72% and 5.48–6.91%, respectively, and the recovery was acceptable. The applicability of the proposed assay was assessed by comparing the determined results with those measured by LC-MS/MS, presenting a satisfactory correlation ( R 2 = 0.9868). The proposed assay, which shows satisfactory analytical performance, has great potential for application in the field of TDM in the future.